1994
DOI: 10.1002/bjs.1800810217
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of outcome using the Mannheim peritonitis index in 2003 patients

Abstract: Early prognostic evaluation of abdominal sepsis is desirable to select high-risk patients for more aggressive therapeutic procedures and to provide objective classification of the severity of disease. The reliability of the Mannheim peritonitis index was assessed and its predictive power for different populations examined in a study of 2003 patients from seven centres in three European countries. The prevalence of risk factors varied considerably between the groups. For a threshold index score of 26, the sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
146
3
11

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(169 citation statements)
references
References 14 publications
9
146
3
11
Order By: Relevance
“…10 In a meta-analysis of results from 7 centers involving 2003 patients, Billing et al reported an average group mortality rate of 2.3% for MPI <21 points, 22.5% at MPI of 21-29 points and 59% with MPI of >29 points. 11 In present study the mean MPI score among the survivor was 27.3, among non-survivor was 33 and overall mean MPI score was 31 (Table 5). Ntirenganya et al in their study the mean MPI was 26.78±6.32 points viz, 10 points as the lowest score and 39 points as the highest score.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…10 In a meta-analysis of results from 7 centers involving 2003 patients, Billing et al reported an average group mortality rate of 2.3% for MPI <21 points, 22.5% at MPI of 21-29 points and 59% with MPI of >29 points. 11 In present study the mean MPI score among the survivor was 27.3, among non-survivor was 33 and overall mean MPI score was 31 (Table 5). Ntirenganya et al in their study the mean MPI was 26.78±6.32 points viz, 10 points as the lowest score and 39 points as the highest score.…”
Section: Discussionsupporting
confidence: 48%
“…In hospital mortality rate in patients with perforation peritonitis ranges between 19% to 60%. 6,7 Outcome of such patients is depends upon several factors related to patients age and sex, disease, co morbidities, time of presentation, therapeutic intervention undertaken and the postoperative complications. 1 Pre-operative assessment by various scoring systems provide the approximate estimates of mortality risk but none have been shown to be sufficiently specific and easy to use on all emergency patients because they require large number of variables to be collected, and few variables like diagnosis of malignancy are not possible everywhere in the emergency setup.…”
Section: Discussionmentioning
confidence: 99%
“…Scoring systems have been developed with parameters including demographic and clinical features. [5][6][7][8] The present study was aimed to assess the utility of Mannheim peritonitis index (MPI) score system in predicting the outcome of patients with perforation peritonitis. study period of 2 years from December 2014 to December 2016 a total of 75 patients with secondary peritonitis were enrolled in the present study after obtaining informed consent.…”
Section: Introductionmentioning
confidence: 99%
“…Long-term survivors have an MPI score of about 20; non-survivors have a score of 33. The MPI is specific for peritonitis and easy to calculate, even during surgery (11,12,13 (14). For patients with a score less than 21 the mean mortality rate was 2.3%, for score 21-29 mortality was 22.5% and for score greater than 29 mortality was 59.1%; the sensitivity was 86%, specificity 74% and accuracy 83% in predicting mortality (14).…”
Section: Introductionmentioning
confidence: 99%
“…The MPI is specific for peritonitis and easy to calculate, even during surgery (11,12,13 (14). For patients with a score less than 21 the mean mortality rate was 2.3%, for score 21-29 mortality was 22.5% and for score greater than 29 mortality was 59.1%; the sensitivity was 86%, specificity 74% and accuracy 83% in predicting mortality (14). Panhofer et al proposed the use of both MPI and APACHE II in patients who developed tertiary peritonitis, concluding that combination of prognostic scores was very useful to detect tertiary peritonitis (15).…”
Section: Introductionmentioning
confidence: 99%